2012
DOI: 10.4244/eijv8i2a41
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal stent deformation: a retrospective analysis of frequency and mechanisms

Abstract: Longitudinal stent deformation can occur secondary to a variety of mechanisms and identification is important as, left untreated, it may be associated with a risk of stent thrombosis. Although seen with several different stents, in our series it was more commonly observed with the Promus Element stent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
114
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(118 citation statements)
references
References 5 publications
1
114
3
Order By: Relevance
“…Furthermore, considerable attention has recently been focused on longitudinal stent deformation (LSD) in patients treated with new-generation thin-strut DES. Williams et al 27 reported 9 cases of LSD during a 4-year period, presenting 0.2% of cases and affecting 0.097% of stents deployed. There were several mechanisms for this complication, including compression by postdilation balloons, guide catheter extensions, and proximal embolic protection devices.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, considerable attention has recently been focused on longitudinal stent deformation (LSD) in patients treated with new-generation thin-strut DES. Williams et al 27 reported 9 cases of LSD during a 4-year period, presenting 0.2% of cases and affecting 0.097% of stents deployed. There were several mechanisms for this complication, including compression by postdilation balloons, guide catheter extensions, and proximal embolic protection devices.…”
Section: Discussionmentioning
confidence: 99%
“…This happens in following clinical scenarios during PCI: (1) crossing the deployed stent with non-compliant balloon for post dilatation, the most commonly reported cause for longitudinal compression, (2) guide catheter or its extensions coming in contact with the stent, either in case of stent in the ostial location or guide catheter deep seating, (3) IVUS catheter pull back for post stent deployment assessment, (4) withdrawal of the stent delivery system following stent deployment when the balloon gets stuck in the struts, (5) crossing the newly deployed stent with another stent for the treatment of a distal lesion, (6) wire entanglement. 2,3,6 These result in either nesting of stent rings into or over each or elongation longitudinally. This phenomenon occurs commonly at the proximal end of the stent and is accentuated by stent malapposition and wire bias toward the outer border of the stent.…”
Section: Discussionmentioning
confidence: 99%
“…With both stent compression and elongation, the vessel is no longer uniformly scaffolded which might compromise the drug delivery and predispose to restenosis. 2,3,6,7 In a clinical study, Micro-Driver deformation was associated with 38% incidence of major adverse cardiac events. 4 Stent deformation once recognized should be corrected by further balloon dilatation to overcome luminal obstruction and apposition of the stent to the vessel wall.…”
Section: Discussionmentioning
confidence: 99%
“…This improves deliverability and conformability, at the expense of reduction in strength. Recently longitudinal shortening has been reported, often associated with adjunctive devices after stent deployment [3][4][5].…”
Section: Case Reportmentioning
confidence: 99%